Effect of conservation treatments on heritage stone. Characterisation of decay processes in a case study. (1st October 2015) - Varas-Muriel, M.J.; Pérez-Monserrat, E.M.; Vázquez-Calvo, C.; Fort, R.
Highlights: Long-term effectiveness, suitability and durability of conservation treatments. Need for preliminary studies to ensure successful restoration. Use of petrological techniques to determine treatment mechanisms. Unsuitable use of cements and synthetic resins on decayed dolostone. Salt-induced loss of restored ornaments. Abstract: Preliminary studies are an imperative when determining the impact of conservation treatments on historical materials. The Romanesque apse on a church at Talamanca de Jarama, Madrid, Spain, whose dolostone was severely decayed by rainwater and salts, was treated in the past with substances that ravaged the restored area. Petrological techniques showed that salts leached out of the cement under the roof onto the stone cornice whose surface had been coated with synthetic resins. During evaporation, the salts precipitated in the stone and underneath the resin, inducing blistering, fissuring, flaking, scaling and detachment of part of the restored decorative elements.